Intercultural communicative competence: Hospitality industry and education perspectives. (June 2022) - Liu, Yunyao; Liu, Jiajie; King, Brian
Abstract: There is scant research on stakeholder perceptions about educational provision for intercultural communicative competences (ICCs), despite increasing recognition of the importance of ICCs in the provision of hospitality. An in-depth exploration of ICC education attributes has examined the perceptions of hospitality stakeholders comprising faculty, students, and professionals in the field. Drawing on 361 valid questionnaires collected in China from faculty members and students of 13 universities and industry professionals employed at 21 hotels, this study used mixed methods to discuss the perceptions of the participants regarding ICCs. The results show that hospitality stakeholders have a range of significantly different insights about intercultural communication attitudes, behaviors, affective communication, and language. The findings have implications for hospitality and tourism educators when developing ICC-related curriculum planning and suggest prospective assistance for developing ICC knowledge and practice among students and industry professionals.